Dating Methods of Pleistocene Deposits and Their Problems: VIII, Weathering - Brookes, Ian (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary This paper reviews the nature and origin of selected weathering features at small and large scales, and their use as indicators of the age of Quaternary glaciated and periglaciated land surfaces. Chemically weathered forms include crystaletching, boulder weathering rinds and surface relief; mechanically weathered forms include degrees of frost-weathering and associated rubble accumulations. Examples of their use as Quaternary geochonometers are drawn mainly from studies in the North American Cordillera and the highlands of eastern Canada. Alternative explanations of weathering differences in the latter area, specifically those emphasizing lithology, weathering environment, and glacial thermodynamics, are summarily reviewed and found to be inadequate when compared to a wealth of independent evidence that affirms the value of weathering features as chronological tools in eastern Canadian highlands, a value long recognized in the Cordillera.